SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM IMPLEMENTASI KURIKULUM JARINGAN SEKOLAH ISLAM TERPADU - Warman; PM Labulan; Jumiati Ulfah (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
This study aims to describe (1) planning, (2) implementation, and (3) evaluation of academic supervision in the implementation of the JSIT curriculum. The research was carried out at SMA IT Daarul Hikmah Bontang. The data collection techniques were through observation interviews and documentation techniques. Data analysis was carried out through data reduction, data display, and verification or concluding stages. The results showed that: (1) Planning for the supervision of SMA IT Daarul Hikmah Bontang in implementing the JSIT curriculum was based on the background, goals, and indicators of academic supervision success. (2) The implementation of the supervision of SMA IT Daarul Hikmah Bontang's implementation of the JSIT curriculum can be seen in the academic supervision instrument. There are indicators regarding the use of the INTEGRATED approach in teaching and learning activities to implement the JSIT curriculum. (3) The evaluation of the principal's academic supervision contained in the report on the results of academic supervision resulted in a follow-up program for teachers to increase knowledge and understanding of the JSIT curriculum